Attitudes towards prenatal diagnosis and abortion in a multi-ethnic country: a survey among parents of children with thalassaemia major in Malaysia - Ngim, Chin Fang (Springer-Verlag, 2013)
Thalassaemia is a public health problem in multi-ethnic Malaysia which mainly affects the Malays, Kadazan-Dusuns and Chinese. This study, the first in Malaysia, aims to evaluate the acceptability of prenatal diagnosis and abortion among Malaysian parents who have a child or children with thalassaemia major and the socio-demographic factors affecting their decision-making. A pre-structured questionnaire was distributed to parents of children with thalassaemia major. Response rate for completed surveys was 99.1 %. Out of 116 respondents, the majority (83/71.6 %) were agreeable for prenatal diagnosis, but only 33 (28.4 %) agreed to both prenatal diagnosis followed by termination of affected foetuses. Of parents who declined abortion, 77.6 % cited religious restriction as the main reason, and their religious background was a significant factor (p = 0.001), with 73.4 % of Muslim participants against termination compared to 25 % of Christians and 13.3 % of Buddhists. Gender, age, highest education level and number of children affected with thalassaemia were non-significant predictors in decision-making regarding abortion. The acceptance rate for termination of foetuses with thalassaemia major in Malaysia is low especially among the Muslims due to religious non-permissibility. Therefore, scholarly deliberations among the Malaysian Muslim religious authorities that result in a supportive stance in this issue may contribute to a more successful prevention programme.